PENERAPAN PELAYANAN PRIMA PADA DONGENG ANAK REMAJA KELILING (DARLING) DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI JAWA TIMUR - Firly Erysa Faldilal Nuraini; Oktarizka Reviandani (Journal Publicuho, 2023)
This research aims to determine the application of excellent service in the Fairy Tales of Traveling Teenagers (Darling) at the East Java Province Library and Archives Service. DARLING (Fairy Tales for Traveling Teenagers) is innovative and provides excellent service for the East Java Province Library and Archives Service. The DARLING program promotes reading and introduces children and teenagers to moving fairy cars. Qualitative descriptive methods were used in this research. The data collection technique uses data triangulation, combining interviews, literature study and documentation. The research results show that DARLING has successfully implemented the A6 principle of excellent service.